2022
DOI: 10.1097/der.0000000000000882
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Venous Blood Leukocyte Profiles and Immunoglobulin E Levels in Atopic Dermatitis Patients

Abstract: BackgroundThere are differing results in the literature regarding the relationship between atopic dermatitis (AD) and peripheral blood leukocyte profiles.ObjectiveThe aim of the study was to investigate the relationship between AD, blood immune cell profiles, and disease severity.MethodsOne hundred AD patients aged 1 month to 18 years without any history of infection or systemic disease were enrolled as the study group. Serum concentration levels of total immunoglobulin E, calculated blood leukocyte profiles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A study (patient group aged between 1 month and 18 years) reported that ELR could be a significant factor in AD diagnosis, similar to our results; however, they also reported higher NLR in the AD group. 21 However, another study (aged 5.6+/-2.8 years) reported no significant difference between the two groups regarding NLR. 22 Another study (60.0±46.5 months-aged patient group) reported increased NLR and PLR in AD but no difference regarding MPV.…”
Section: Discussionmentioning
confidence: 91%
“…A study (patient group aged between 1 month and 18 years) reported that ELR could be a significant factor in AD diagnosis, similar to our results; however, they also reported higher NLR in the AD group. 21 However, another study (aged 5.6+/-2.8 years) reported no significant difference between the two groups regarding NLR. 22 Another study (60.0±46.5 months-aged patient group) reported increased NLR and PLR in AD but no difference regarding MPV.…”
Section: Discussionmentioning
confidence: 91%